Research for the Investigation of Consumer Attitudes towards Online Shopping in Niğde Province (International Journal of Scientific Research and Management (IJSRM), 2018)
This research study is conducted to determine consumers’ reasons for not shopping online, to explicate their attitudes towards online purchasing behaviors, and to examine whether or not their attitudes towards online purchasing behavior differ in accordance with the descriptive characteristics of the consumers. The survey questionnaires, prepared in compliance with the aim, are conducted on 502 Niğde residents chosen by convenience sampling method. The data obtained from the survey questionnaires are analyzed via SPSS 22.0 computer software. According to the results of the study; the reasons that cause online shopping include price reduction, the economics of time and finding the best product, while the reasons of avoiding online shopping include refraining from giving out identity document and credit card information, and demanding physical product trial. Participants are determined to be such individuals within a certain age range (26-35 years) who have more positive attitudes towards online shopping rather than negative attitudes, have higher education and income levels. In the research study, it is also detected that gender, the location at which the Internet is connected, and the duration of time spent on the Internet are independent of attitudes towards online shopping.